Repeated mild traumatic brain injury in female rats increases lipid peroxidation in neurons - Yates, N.; Lydiard, S.; Fehily, B.; Weir, G.; Chin, A.; Bartlett, C.; Alderson, J.; Fitzgerald, Melinda (Springer-Verlag, 2017)
Negative outcomes of mild traumatic brain injury (mTBI) can be exacerbated by repeated insult. Animal models of repeated closed-head mTBI provide the opportunity to define acute pathological mechanisms as the number of mTBI increases. Furthermore, little is known about the effects of mTBI impact site, and how this may affect brain function. We use a closed head, weight drop model of mTBI that allows head movement following impact, in adult female rats to determine the role of the number and location of mTBI on brain pathology and behaviour. Biomechanical assessment of two anatomically well-defined mTBI impact sites were used, anterior (bregma) and posterior (lambda). Location of the impact had no significant effect on impact forces (450 N), and the weight impact locations were on average 5.4 mm from the desired impact site. No between location vertical linear head kinematic differences were observed immediately following impact, however, in the 300 ms post-impact, significantly higher mean vertical head displacement and velocity were observed in the mTBI lambda trials. Breaches of the blood brain barrier were observed with three mTBI over bregma, associated with immunohistochemical indicators of damage. However, an increased incidence of hairline fractures of the skull and macroscopic haemorrhaging made bregma an unsuitable impact location to model repeated mTBI. Repeated mTBI over lambda did not cause skull fractures and were examined more comprehensively, with outcomes following one, two or three mTBI or sham, delivered at 1 day intervals, assessed on days 1–4. We observe a mild behavioural phenotype, with subtle deficits in cognitive function, associated with no identifiable neuroanatomical or inflammatory changes. However, an increase in lipid peroxidation in a subset of cortical neurons following two mTBI indicates increasing oxidative damage with repeated injury in female rats, supported by increased amyloid precursor protein immunoreactivity with three mTBI. This study of acute events following closed head mTBI identifies lipid peroxidation in neurons at the same time as cognitive deficits. Our study adds to existing literature, providing biomechanics data and demonstrating mild cognitive disturbances associated with diffuse injury, predominantly to grey matter, acutely following repeated mTBI.